Dryobalanoxylon sp. : a fossil wood preserved in the Genteng Formation from Lebak Regency, Banten Province, Indonesia - oktariani, Hanny; Winantris, .; Fauzielly, Lili; Damayanti, Ratih (Faculty of Geological Engineering, Universitas Padjadjaran, 2017)
The fossilized wood unearthed in Sindangsari Village, Sajira District, Lebak Regency, Banten Province, Indonesia. The depositional environment of this Early Pliocene fossilized wood that has been found in tuff sediment of Genteng Formation corresponds littoral to terrestrial deposition. To identify a fossil wood type, preparation made from three sides; transverse, radial and tangential. The preparation of thin section following to the one method in the rock petrography. Anatomical features of the fossil wood are as follows : wood porous diffuse, vessel almost exclusively solitary with 7 – 14 / mm2, ray width 1 to 3 cells, larger rays commonly 4 to 10 seriate, body ray cells procumbent with one row of upright and/or square marginal cells, axial canals in long tangential lines, prismatic crystals in parenchyma cells. These features show affinities of the fossil wood to Dryobalanoxylon member of family Dipterocarpaceae.